Conflict in cyber space theoretical, strategic and legal perspectives - Friis, Karsten; Ringsmose, Jens (Routledge studies in conflict, security and technology, 2016)
Adopting a multidisciplinary perspective, this book explores the key challenges associated with the proliferation of cyber capabilities. By asking important strategic questions on the theoretical, strategic, ethical and legal implications and challenges of the proliferation of cyber warfare capabilities, the book seeks to stimulate research into an area that has hitherto been neglected.